2015
DOI: 10.12965/jer.150198
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill exercise decreases incidence of Alzheimer’s disease by suppressing glycogen synthase kinase-3β expression in streptozotocin-induced diabetic rats

Abstract: Diabetes is a metabolic disorder, and it is considered as a major risk factor for Alzheimer’s disease (AD). In the present study, we evaluated whether treadmill exercise ameliorates progression of AD in relation with glycogen synthase kinase-3β (GSK-3β) activity using streptozotocin (STZ)-induced diabetic rats. For this study, step-down avoidance task, immunohistochemistry for glycogen synthase kinase-3β (GSK-3β) and tau, and western blot for phosphor-phosphoinositide 3 kinase (p-PI3K)/PI3K and phosphor-Akt (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…3), but no deposits of Congophilic materials (amyloid plaques) were observed. Moreover, although findings from the studies of Kim et al (2015) showed the presence of neurofibrillary tangle in the hippocampus of rats with STZinduced DM-associated AD pathology, the degree of prefrontal tau hyperphosphorylation associated with our AD + DM model is unclear as staining for phosphorylated tau could not be done.…”
Section: Discussionmentioning
confidence: 84%
“…3), but no deposits of Congophilic materials (amyloid plaques) were observed. Moreover, although findings from the studies of Kim et al (2015) showed the presence of neurofibrillary tangle in the hippocampus of rats with STZinduced DM-associated AD pathology, the degree of prefrontal tau hyperphosphorylation associated with our AD + DM model is unclear as staining for phosphorylated tau could not be done.…”
Section: Discussionmentioning
confidence: 84%
“…Kang and Cho [39] found that 6 weeks of treadmill exercise upregulates the level of p-InR, p-PI3K, and p-Akt in the brains of AD rats. Kim et al [40] found that 12 weeks of aerobic treadmill exercise also significantly increases the levels of p-PI3K and p-Akt in the hippocampus of diabetic rats. In addition, 6 weeks of exercise increases the number of p-mTOR-positive neurons and astrocytes in the striatum, hippocampus, and amygdala of normal rats compared with the static control group [41].…”
Section: Discussionmentioning
confidence: 99%
“…To induce diabetes, a single intraperitioneal injection of STZ (50 mg/kg, dissolved in 0.01-M citrate buffer at pH 4.5; Sigma Chemical Co.) was given to each animal, as the previously described method ( Kim et al, 2015 ). Blood glucose levels were determined 3 days after STZ injection using a blood glucose tester (Arkray, Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%